2014
DOI: 10.1186/bf03352313
|View full text |Cite
|
Sign up to set email alerts
|

Crustal strain field in the Deccan trap region, western India, derived from GPS measurements

Abstract: Global Positioning System (GPS) measurements were made to estimate the crustal deformation strain rate for the Deccan trap region, western India. Estimated horizontal velocity vectors in ITRF96 are in the range of 40-60 mm/yr with an average of 51 mm/yr in N47• E. Using the horizontal components of the velocity vectors, strain field has been estimated by the Least Square Prediction (LSP) method. An extension is observed along the west coast and south of Koyna and Warna reservoirs, transcending in to a region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Evidence for flexure: GPS observations along the west coast of India and other geological studies Reddy et al (2000) reported the results of Global Positioning System (GPS) measurements in the western Maharashtra between latitude 16°N and 21°N and longitude 72°E and 75°E. They observed some differences in displacement fields between sites that are located on either side of the WGE.…”
Section: Stresses Near Passive Marginsmentioning
confidence: 92%
“…Evidence for flexure: GPS observations along the west coast of India and other geological studies Reddy et al (2000) reported the results of Global Positioning System (GPS) measurements in the western Maharashtra between latitude 16°N and 21°N and longitude 72°E and 75°E. They observed some differences in displacement fields between sites that are located on either side of the WGE.…”
Section: Stresses Near Passive Marginsmentioning
confidence: 92%
“…Geodetic measurements in the Deccan trap region (16 • -21 • N; 73 • -75 • E) of western India estimated the strain rate for crustal deformation with reference to the horizontal velocity vectors in the International Terrestrial Reference Frame'96 (ITRF96). It occurs in the range of 40-60 mm/year with an average of 51 mm/year in N47 • E direction (Reddy et al, 2000). Padhy and Crampin (2006) discussed shear-wave splitting characteristic of local earthquakes in the aftershock zone of the Bhuj earthquake.…”
Section: Stress Distribution In Kachchhmentioning
confidence: 99%
“…Latur earthquake (Mw 6.3) of 29 September, 1993 is considered as typical stable continental region events. GPS measurements made by Reddy et al (2000) in Deccan trap region, western India suggested an extensional strain regime observed along the west coast and south of Koyna and Warna reservoirs, transcending into a region of compressive strain towards the interior of the shield area. Two failed rift zones specifically Narmada-Son-Tapti and Godavari rift zone also play an important role in crustal deformation in peninsular India.…”
Section: Gps Measurements In Indian Plate Interior Regionmentioning
confidence: 97%